Paramedics' understandings of managing personal reactions during emergency responses : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, New Zealand - Ryburn, Annabelle (Massey University, 2011)
The repeated exposure to potentially traumatic experiences is inherent within the field of emergency response work. Traditionally research focuses on what responders do to ‘cope’ with their reactions during emergency responses, and attempts to predict which ‘personality types’ may ‘cope’ better with this repeated exposure. This type of research leads to recommendations of ‘best practice coping’, which are often based on theoretical models of emotional processing and devoid of contextual relevance. This study investigated further than what responders do to manage reactions, and sought to understand how and why. It utilised individual interviews, focus groups and ambulance shift observation to explore how a group of St John paramedics constructed managing their reactions during and after emergency response situations. The study examined how reaction management is understood, and what options are perceived to be accessible when social, historical and cultural contexts are considered. The findings revealed that the paramedics’ discursive constructions regarding reaction management related to four key areas of understanding. These areas corresponded to the chronological process of emergency responding. The paramedics’ constructions started with conceptualisations of their job role and the expectations that came with it, then evolved through to incident response, post-incident reflection, and finally to support-seeking. The findings across these areas suggest that strategies described in previous research as ‘negative’ or ‘risky’ are oversimplifications. These individual strategies often exist as a component of a broader strategy to facilitate functioning in a response situation. It was concluded that the most important element of reaction management for the paramedics was ability to find acceptance for response incident outcomes. This understanding shifted the ‘problem area’ into the post-incident timeframe and onto issues of accessibility and acceptability of using peer and psychological support to facilitate acceptance. The implications of this research include understanding the necessity for tailored psychoeducation regarding reaction management at St John which is both functionally and contextually relevant. Additionally, the research highlights the need to address the ‘social risks’ attached to support-seeking at the St John organisation.
Keywords: Emergency response work; Coping; Resilience; Trauma; Paramedics; Emotional reactions; Reaction management